Azhar-ul-lughat: jadeed urdu - Bhatti, Muhammad Saqlain; Naqvi, Syed Slwat Ali (Azhar publishers Lahore, 2008)
"Azhar Ul Lughat Jadeed" is a contemporary Urdu dictionary published by Azhar Publishers. It offers a comprehensive collection of words, phrases, and their meanings, making it an invaluable resource for students, writers, and anyone looking to enhance their Urdu vocabulary. The dictionary is designed to be user-friendly, with clear definitions and examples, catering to both novice and advanced speakers. It also includes modern terminology and expressions, reflecting current usage in the Urdu language. Overall, it serves as a vital tool for effective communication and language learning.